Estimation of genetic parameters for weight traits and Kleiber Index in a Brahman cattle population - Manuel, Matos [UNESP]; Cavani, Ligia [UNESP]; Millen, Danilo Domingues [UNESP]; Andrighetto, Cristiana [UNESP]; Lupatini, Gelci Carlos [UNESP]; Fonseca, Ricardo da [UNESP] (Univ Sao Paolo, 2019)
Interest in improving feed efficiency of cattle has been increasing. The residual feed intake (RFI), the most commonly used measurement of feed efficiency, is expensive and can only be used in a small number of animals. The Kleiber Index has also been proposed to measure RFI. In this study, we estimated genetic parameters for the Kleiber Index average daily weight gain and adjusted weights to obtain a more comprehensive understanding of potential responses to selection and support the development of breeding strategies. Genetic analyses were conducted on animal records from a data file with 36,505 animals recorded by ABCZ (Brazilian Association of Zebu Breeders). Restricted maximum likelihood estimates of genetic parameters were computed with Wombat software. Heritabilities ranged from 0.24 to 0.22 for adjusted weights, from 0.12 to 0.26 for Kleiber Indexes and from 0.15 to 0.22 for average daily gains. Correlations between traits ranged from -0.06 to 0.99. Results indicated that Kleiber Indexes at different ages do not constitute a viable solution for the selection of bulls and cows for Brazilian Brahman populations in terms of feeding efficiency.
Keywords: genetic correlation; average daily gain; heritability; standard age weight